Studi Faktor-Faktor yang Berhubungan dengan HIV pada Perempuan di Kalimantan Barat, Indonesia - Hairunisa, Nany; Sabrina, Isra; Amalia, Husnun; Mashabi, Yasmine; Zaina, Nashita Amira; Yousif, Emad (Fakultas Kedokteran Universitas Trisakti, 2023)
Background According to national data, West Kalimantan is one of the ten top provinces that reported AIDS cases, ranked eighth. Until December 2019, based on data recorded in the Provincial Health Office that reported to the Indonesia Ministry of Health, the AIDS case rate in West Kalimantan was 49.35, showing over the national AIDS case rate (38.93). In this study, an unmatched case-control determines the factors associated with HIV/AIDS among women in West Kalimantan, Indonesia. Methods The study was conducted among 90 women who tested positive for HIV/AIDS (cases) and 90 who tested negative for HIV/AIDS (controls). Data were collected using questionnaires from June 2019 to August 2019 at three community health centres in West Kalimantan. Data were analyzed using IBM Statistical Package Social Science (SPSS) 19. Descriptive analyses and Multivariate logistic regression analysis were used to examine the factors associated with HIV/AIDS. Results: This study has found a significant association between crucial aspects such as marital status, occupation, knowledge about HIV/AIDS, HIV treatment, and VCT (Voluntary Counseling and Testing) service program with cases of HIV/AIDS. A significant association between marital statuses with HIV/AIDS suggests that divorced/widowed have a higher risk of having HIV/AIDS, followed by the married group. Women with good educational backgrounds will likely know how to prevent HIV infection and take preventive measures to protect themselves. Results This study found a significant relationship between several important aspects such as marital status, occupation, knowledge of HIV/AIDS, HIV treatment, and the VCT (Voluntary Counseling and Testing) service program with HIV/AIDS cases. The significant relationship between marital status and HIV/AIDS shows that divorced/widows have a higher risk of contracting HIV/AIDS, followed by the married group. Women with a good educational background tend to know about HIV infection prevention measures and take precautions to protect themselves. Conclusions Some factors are significantly related to HIV/AIDS. Thus, educating women about sex could potentially decrease the number of HIV/AIDS cases.